Differences in Health Care Expenditures Among Non-Latino Whites and Asian Subgroups Vary Along the Distribution of the Expenditures. (August 2021) - Park, Sungchul; Chen, Jie; Roby, Dylan H.; Ortega, Alexander N.
Using a nationally representative sample from the 2013 to 2016 Medical Expenditure Panel Survey, we examined differences among non-Latino Whites and Asian subgroups (Asian Indians, Chinese, Filipinos, and other Asians) across distributions of total health care expenditures and out-of-pocket (OOP) expenditures. For total health care expenditures, differences between Asian and White adults persisted throughout the distribution, but the magnitude of the difference was larger at no or low levels of expenditures than at high expenditure levels. A similar pattern was observed in OOP expenditures, but the magnitude of the difference was substantially larger at low levels of expenditures. The extent of the difference varied by Asian subgroup, but this trend persisted across all the subgroups. Similar trends were observed by nativity and limited English proficiency. Our findings suggest that differences in health care expenditures between Whites and Asians are more pronounced at low expenditure levels.